Dwor - Singer, Isaac Bashevis, 1904-1991; Wyrzykowska, Irena (Warszawa : Warszawskie Wydawn. Literackie Muza Sa, 1999)
Polish translation of "Hoyf", known in English under title "The manor". A story of Jewish life and conflict in Poland during the 19th century.
Keywords: Jews -- Poland -- Fiction; Poland -- History -- 1864-1918 -- Fiction